Dietary therapy in abdominal aortic aneurysm — Insights from clinical and experimental studies - Yin, Li; Gregg, Alexander Christopher; Riccio, Alessandra Marie; Hoyt, Nicholas; Islam, Zain Hussain; Ahn, Jungeun; Le, Quang; Patel, Paranjay; Zhang, Mengxue; He, Xinran; McKinney, Matthew; Kent, Eric; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abdominal aortic aneurysm (AAA) is a prevalent vascular disease with high mortality rates upon rupture. Despite its prevalence in elderly populations, there remain limited treatment options; invasive surgical repair, while risky, is the only therapeutic intervention with proven clinical benefits. Dietary factors have long been suggested to be closely associated with AAA risks, and dietary therapies recently emerged as promising avenues to achieve non-invasive management of a wide spectrum of diseases. However, the role of dietary therapies in AAA remains elusive. In this article, we will summarize the recent clinical and pre-clinical efforts in understanding the therapeutic and mechanistic implications of various dietary patterns and therapeutic approaches in AAA.